Polycarp and Paul : an analysis of their literary and theological relationship in light of Polycarp's use of biblical and extra-biblical literature - Berding, Kenneth. (Vigiliae Christianae, Supplements, 2002)
This volume addresses the question of the Apostle Paul's literary and theological influences on Polycarp of Smyrna. To this end, the most detailed analysis in print of Polycarp's dependence on earlier literature--both biblical and extra-biblical--is undertaken in the first part of the book. This general analysis forms the basis for the study of three questions: 1) Is Polyarp an imitator of Paul? 2) Whom does Polycarp think is the author of the Pastoral Epistles? 3) To what degree is Polycarp influenced by the theology of Paul? This volume will be of particular interest to anyone studying the Apostolic Fathers, the reception of Paul in the second century, the concept of imitation, and the authorship of the Pastoral Epistles.